The response mechanisms of industrial Saccharomyces cerevisiae to acetic acid and formic acid during mixed glucose and xylose fermentation. (April 2020) - Li, Bo; Xie, Cai-Yun; Yang, Bai-Xue; Gou, Min; Xia, Zi-Yuan; Sun, Zhao-Yong; Tang, Yue-Qin
Graphical abstract: Highlights: Response mechanisms to weak acids were first revealed in mixed sugars fermentation. Synergistic inhibition of acetic acid and formic acid on S. cerevisiae was serious. Three transcription factors related to acetic and formic acids stress were proposed. Abstract: The growth and ethanol fermentation of Saccharomyces cerevisiae are vulnerable to weak acid that coexists with sugar in lignocellulosic hydrolysate. In this study, the molecular basis of S. cerevisiae in response to acetic and formic acids was investigated when fermented with glucose and xylose at pH 5.0. Transcriptional profiling revealed that 294 (657 in total) differentially expressed genes (DEGs) were exclusive to mixed acetic and formic acids (Aa_Fa) group, the DEGs in acetic acid (Aa) and formic acid (Fa) group were 308 and 326, respectively. The general responses to Aa, Fa, and Aa_Fa mainly involved carbohydrate metabolism, amino acid metabolism, transcriptional regulation, and stress response. In Aa_Fa group, the enrichment ratio of each pathway was much higher than being exposed to Aa or Fa stress individually, and some enrichments not existed in Aa or Fa group were observed, suggesting the synergistic anti-inhibition responses of S. cerevisiae was triggered. In yeast cells, bioconversion, stress response, and transmembrane transport could be activated to resist acetic and formic acids accompanying with energy consumption. Except the putative transcriptional factor (TF) - Haa1p, the other three TFs, Hap4p, Yox1p, and Mag1p, might as well be considered to participate in acetic and formic acids resistance responses.